MR imaging of skeletal muscle signal alterations: Systematic approach to evaluation. Issue 5 (May 2016) - Kumar, Yogesh; Wadhwa, Vibhor; Phillips, Lauren; Pezeshk, Parham; Chhabra, Avneesh
Highlights: Muscle denervation or myopathy from different causes can appear similar on conventional MRI. Advanced MRI techniques for characterizing muscle edema play complementary role. DWI and CSI are useful especially if intravenous contrast cannot be administered. A systematic assessment approach is needed for muscle pathology characterization. Abstract: Muscle edema or edema-like signal alterations are commonly encountered findings in musculoskeletal magnetic resonance (MR) imaging. Although such signal alterations are very sensitive for detection of the underlying muscle pathology, these are often non-specific findings. Encompassing knowledge of their typical clinical presentations, characteristic appearances and patterns of muscle signal alterations and following a systematic approach towards their assessment, a reader can effectively narrow down the differential diagnosis. This article outlines the role of conventional imaging and advanced anatomic and functional musculoskeletal MR imaging techniques in the evaluation of various muscle disorders and presents a systematic approach towards their diagnosis and management.